Pelatihan Menggambar Teknik Bagi siswa SMK Pelayaran Jakarta Raya - Kiswiru Yudha Ningsih; Ike Arriany; Junadi (Paramacitra Jurnal Pengabdian Masyarakat, 2023)
Concepts and ideas are still abstract if they only exist in the mind, then they can be realized after being outlined in the form of a sketch until then refined according to the goal. In the world of engineering, drawings play an important role in the design and planning process before entering the manufacturing and assembly stages. With pictures, the constituent components, codes and symbols, sizes, ports, connecting lines can be seen more objectively. The subject of technical drawing has been a mandatory material for students in several vocational schools for a long time, but it is still in the form of 2D manual sketch drawings and not computer based. The increasingly rapid technological developments of course have an impact on the world of business and industry as a market for vocational school graduates. Improving the quality of education and human resources is of course a necessity to produce quality vocational school graduates who meet market needs, in line with INPRES No. 9 of 2016 concerning vocational school revitalization. Manual sketch drawings are still needed, but for results that are closer to reality, they need to be converted into 3D images which can even be printed directly using a 3D printer so that the design results that have been created can be directly corrected. One software that can be used to design 3D images is Autodesk Inventor.